THE STARLING PHENOMENON: A CASE STUDY OF ITINERANT INSTANT DRINK VENDORS IN TANGERANG REGENCY - Yulius, Kevin Gustian; Titus David Fandika; Vasco A.H. Goeltom (Jurnal Industri Kreatif dan Kewirausahaan, 2025)
This study explores the operations of Starling vendors—informal mobile sellers of instant beverages in Gading Serpong, Tangerang Regency—who represent a unique form of ultra-micro enterprise within the suburban informal economy. As urban spaces expand and formal employment remains limited, these vendors have emerged as resilient actors navigating a dynamic environment through mobility, adaptability, and customer proximity. The study aims to examine how Starling vendors sustain their businesses through operational strategies, product diversification, and customer targeting. A qualitative case study method was used, involving semi-structured interviews with ten Starling vendors, direct field observations, and document analysis. Thematic analysis was employed to extract patterns in vendor practices, customer interactions, and environmental challenges. The results show that Starling vendors demonstrate entrepreneurial agility by adjusting working hours, alternating between mobile and stationary operations, and diversifying their offerings beyond instant coffee to include snacks and cigarettes. Most customers are online motorcycle taxi drivers, office workers, and students, with cash still dominating payment methods. Key challenges include weather disruptions and spatial insecurity due to the absence of vendor-friendly policies. The study concludes that Starling vendors exemplify how ultra-micro businesses in suburban areas survive by leveraging informal infrastructures and local networks. While limited in scope, this research offers policy insights for enhancing vendor sustainability through support in digital payments, infrastructure access, and hygiene practices. Future studies should include consumer and policymaker perspectives to address public health and environmental concerns in informal mobile vending.